Sutika Swasthavrittam with Critical Review of Comprehensive Approaches through Various Samhitas - Meemansa; Saini, Manish Kumar (International Research Journal of Ayurveda & Yoga, 2020)
Sutika-Swasthavrittam or Paricharya ( Post natal care) is a special regimen provided by ancient classics that should be followed by Sutika. Healthy generation is the productivity of a healthy environment of world. Pregnancy is a state or journey in woman’s life impacting all her body and mind. Healthy pregnancy outcome is also in the mindset of woman. As healthy postnatal or puerperal period is also having a major role in concern to health of lady, Ayurveda science gives equal importance to antenatal and postnatal period. The puerperal woman is known as Sutika. A proper diet regimen (Ahara) and life style (Vihara) also explained in terms of Sutika Swasthavrittam to purificate the remaining doshas and to restore and to rejuvenate the Dhatus of the Puerperal woman. Specifically Acharya Kashyap has explained the Desha wise regimen for Sutika, sex of baby wise regimen also. In present study a review through all Brihtrayi Granthas, Kashyap Samhita, Bhavaprakasha, Harita Samhita, Bhaishajya Ratnavali, Yogaratnakara is done